(untitled) (World Bulletin of Education and Learning, 2025)
This article examines the scientific and philosophical views of the Jadid movement regarding the role of enlightenment and education in fostering cultural advancement within Central Asian society. The study highlights how Jadid intellectuals sought to modernize traditional educational institutions, introduce secular sciences, and cultivate analytical and critical thinking among the younger generation. Their efforts in reforming the curriculum, promoting modern pedagogical methods, and establishing new-type schools (usul-i jadid) played a decisive role in expanding cultural consciousness, strengthening national identity, and laying the foundations for societal modernization.